Tubular direct carbon SOFC with ceramic separation membrane to remove CO2 - Shao, Zongping (Elsevier Ltd, 2015)
A Chinese/Australian research team has created an anode-supported tubular solid oxide fuel cell that functions as a carbon fuel container as well as an electrochemical device for power generation. The tubular SOFC uses an integrated ceramic membrane to separate CO2 and CO, facilitating the development of a high power density SOFC that directly uses carbon as a fuel source.